Potential barriers towards optimal medication adherence in out-patients with stable coronary artery disease - S. B. Fitilev; A. V. Vozzhaev; I. I. Shkrebniova; D. A. Kliuev; A. O. Ovaeva (Izdatelstvo OKI, 2023)
Introduction. The results from foreign and local studies demonstrate that more than a half of patients with cardiovascular diseases do not take medication in compliance with doctors' recommendations. The search for signiﬁcant barriers to optimal medication adherence might improve the development of adherence control measures in patients with stable coronary artery disease (SCAD) in routine clinical practice of primary care.Aim. To study the nature and incidence of potential barriers to optimal medication adherence and their association with social and demographic parameters in patients with SCAD.Methods. This publication describes the fragment of the study "PHARMCARE" in which 123 coronary patients were included. Data on demography, social status, medical history and pharmacotherapy were registered. The barriers to medication adherence were identiﬁed by means of validated scale (questionnaire) SEAMS (Self-Eﬃcacy for Appropriate Medication Use Scale). Data analysis was conducted by descriptive statistics and regression modeling.Results. The analysis of incidence of barriers to medication adherence allowed to identify the list of most signiﬁcant ones: "fear of side eﬀects", "intake of several diﬀerent medicines each day", "intake of medicines more than once a day", "medicines look diﬀerent than usual", "normal routine gets messed up", "busy day planned", "no one reminds to take medicines" and "staying away from home". More than a third of all the respondents reported at least one of barriers (37%), that was in major cases "fear of side eﬀects" (22%). Linear one-factor modeling revealed association of number of signiﬁcant barriers in patients with level of their education (р=0,009) and presence of partner or caregiver (р=0,001), that was also conﬁrmed by the multivariate model. Less barriers were identiﬁed in coronary patients that had partner or caregiver (р=0,009) and higher education (р=0,045).Conclusion. The study results revealed that the signiﬁcant barriers to optimal medication adherence in out-patients with SCAD were related either to patients' behavior or to pharmacotherapy proﬁle. Uncertainty in overcoming barriers was most typical for single patients without higher education. The obtained results should be taken into consideration when develop strategies for improvement of medication adherence in patients with SCAD in primary care practice.